Comparison between the effects of ultrasound guided intra-articular injections of platelet-rich plasma (PRP), high molecular weight hyaluronic acid, and their combination in hip osteoarthritis: a randomized clinical trial - Farshad Nouri; Marzieh Babaee; Parya Peydayesh; Hadi Esmaily; Seyed Ahmad Raeissadat (BMC Musculoskeletal Disorders, 2022)
Abstract Background Intra articular (IA) injection of platelet-rich plasma (PRP) and hyaluronic acid (HA) are of the new methods in the management of hip osteoarthritis (OA). The aim of this study was to compare the effectiveness of IA injections of PRP, HA and their combination in patients with hip OA. HA and PRP are two IA interventions that can be used in OA in the preoperative stages. Due to the different mechanisms of action, these two are proposed to have a synergistic effect by combining. Methods This is a randomized clinical trial with three parallel groups. In this study, patients with grade 2 and 3 hip OA were included, and were randomly divided into three injection groups: PRP, HA and PRP + HA. In either group, two injections with 2 weeks’ interval were performed into the hip joint under ultrasound guidance. Patients were assessed before the intervention, 2 months and 6 months after the second injection, using the visual analog scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and Lequesne questionnaires. Results One hundred five patients were enrolled randomly in HA, PRP and PRP + HA groups. All three groups showed significant improvement in WOMAC, VAS, and Lequesne at 2 months and 6 months compared with baseline. Comparison of the 3 groups demonstrated significant differences regarding WOMAC and Lequesne total scores and the activities of daily living (ADL) subscale of Lequesne (P = 0.041, 0.001 and 0.002, respectively), in which the observed improvement at 6th month was significantly higher in the PRP + HA and PRP groups compared to the HA group. Conclusion Although all 3 interventions were associated with improvement of pain and function in patients with hip OA, the therapeutic effects of PRP and PRP + HA injections lasted longer (6 months), and the effects of these two interventions on patients’ performance, disability, and ADL were superior to HA in the long run. Moreover, the addition of HA to PRP was not associated with a significant increase in the therapeutic results. Trial registration The study was registered at Iranian Registry of Clinical Trials (IRCT) website http://www.irct.ir/ , a WHO Primary Register setup, with the registration number of IRCT20130523013442N30 on 29/11/2019.